PENGARUH DISIPLIN KERJA, BUDAYA ORGANISASI, DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SEKOLAH DASAR SWASTA DI JAKARTA UTARA - Maria Adventina Disne; Tin Agustina K; Asriana Kibtiyah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Education is one of the most important factors in developing quality human resources. In realizing quality education, one of the main aspects that needs to be considered is teacher performance. Teacher performance can be influenced by work discipline, organizational culture and work motivation. The purpose of this study is to determine and analyze 1) The effect of work discipline on teacher performance in Private Elementary Schools in North Jakarta. 2) The effect of organizational culture on teacher performance in Private Elementary Schools in North Jakarta. 3) The effect of work motivation on teacher performance in Private Elementary Schools in North Jakarta. 4) The effect of work discipline, organizational culture and work motivation simultaneously on teacher performance in Private Elementary Schools in North Jakarta. This study uses a quantitative approach with a survey method by distributing questionnaires to 61 teachers of Private Elementary Schools in North Jakarta Branch with a saturated sampling technique. Data analysis was carried out using multiple linear regression tests to see the partial and simultaneous effects of independent variables on the dependent variable. The results of the study show that 1) work discipline has a partial significant influence on the performance of teachers at the North Jakarta Branch of Private Elementary Schools, 2) organizational culture does not have a partial significant influence on the performance of teachers at the North Jakarta Branch of Private Elementary Schools, 3) work motivation does not have a partial significant influence on the performance of teachers at the North Jakarta Branch of Private Elementary Schools, 4) simultaneously, the variables of work discipline, organizational culture, and work motivation simultaneously have a significant influence on the performance of teachers at the North Jakarta Branch of Private Elementary Schools.